ALGEBRAIC MULTIGRID PRECONDITIONER FOR SECOND ORDER FINITE ELEMENT APPROXIMATIONS IN RECTANGULAR DOMAINS I. TWO-LEVEL PRECONDITIONER - Hakopian, Yu. R.; Hovhannisyan, H. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The present paper, consisting of two parts, is devoted to constructing an algebraic multigrid preconditioner for stiffness matrices arising in second-order finite element approximation of elliptic boundary value problems. In the first part a two-level preconditioner, on the base of which the multigrid preconditioner will be constructed, is described.